Preoperative Imaging and Online Photo Galleries: The #Key to Surgical Commitment - Givens, Victoria B.; Perkins, Stephen W. (The Surgery Journal, 2021)
Importance Preoperative imaging provides an advantageous balance by helping patients to effectively communicate their aesthetic desires while allowing surgeons to establish realistic expectations of surgical outcomes.Objective To determine the role of preoperative imaging and the importance of online-based photo galleries in influencing a patient's decision to pursue cosmetic facial plastic surgery.Design, Setting, and Participants A retrospective study was conducted on 100 patients who underwent preoperative imaging prior to undergoing aesthetic facial plastic surgery from July 2019 to May 2020. An in-office physician-led clinical consultation followed by a preoperative imaging session was performed on each patient prior to surgical intervention. A 6-question survey was provided once to all patients between their 3- and 12-month postoperative time periods.Main Outcomes and Measures The importance of preoperative imaging and the influence of physician website and social media photo galleries regarding surgical decision-making was evaluated.Results A total of 100 participants (female [90; 90%]) and mean age 52.6 (range, 18–77) years were included. Nearly 60% of patients underwent facial rejuvenation procedures. All reported that preoperative in-office physician consultation in combination with the use of preoperative imaging were helpful in facilitating a commitment to surgical intervention. Sixty-nine (69%) patients endorsed the use of both the frontal and lateral imaging views, while 30 (30%) deemed a single angle to be superior. Seventy (70%) participants utilized online-based “before & after” photo galleries in the form of physician websites and/or social media platforms to assist in their decision to undergo surgical intervention.Conclusions and Relevance The combination of in-office physician consultation, preoperative imaging, and availability of website and/or social media photo galleries plays a key role in a patient's decision to pursue cosmetic surgery. Thus, implementation of all facets should become an integral part of any facial plastic surgeon's aesthetic practice.
Keywords: preoperative imaging; facial rejuvenation; rhinoplasty; social media; surgical commitment